2014
DOI: 10.1155/2014/520124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cooling on Ankle Muscle Strength, Electromyography, and Gait Ground Reaction Forces

Abstract: The effects of cooling on neuromuscular function and performance during gait are not fully examined. The purpose of this study was to investigate the effects of local cooling for 20 min in cold water at 10°C in a climate chamber also at 10°C on maximal isometric force and electromyographic (EMG) activity of the lower leg muscles. Gait ground reaction forces (GRFs) were also assessed. Sixteen healthy university students participated in the within subject design experimental study. Isometric forces of the tibial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
5
1
1
Order By: Relevance
“…In contrast to this study and others mentioned above, Halder et al 15 investigated the effect of cooling in MVIC of anterior tibialis and gastroc-nemius muscles using a dynamometer and found a significant reduction in anterior tibial strength. It is noteworthy that in this study, sample had legs submerged for 20 minutes in water at 10°C in a climate chamber also at 10°C.…”
Section: Discussioncontrasting
confidence: 90%
“…In contrast to this study and others mentioned above, Halder et al 15 investigated the effect of cooling in MVIC of anterior tibialis and gastroc-nemius muscles using a dynamometer and found a significant reduction in anterior tibial strength. It is noteworthy that in this study, sample had legs submerged for 20 minutes in water at 10°C in a climate chamber also at 10°C.…”
Section: Discussioncontrasting
confidence: 90%
“…Muscle temperature can also influence maximal strength. Cooling by submersion of a limb in cold water (3-15°C) for~2 0 min decreases strength 10 -40% (41,80,88,90,96,111,149,167,185,189,261,332). However, warming by submersion of a limb in hot water (40°C) for 20 -40 min does not affect maximal strength (80,90,185,380).…”
Section: Administrative Strategies and The Test Environmentmentioning
confidence: 96%
“…The significant functional improvement in ankle dorsiflexion ROM in patients of the studied groups is consistent with Boudarham et al who revealed that hemiplegic patients with spastic foot equinus improved their gait after wearing the ankle foot orthosis. It was found that the increase in ankle dorsiflexion during the stance and swing phases was the main adaptation in the measured spatiotemporal parameters of patients' ambulation [17]. The improvement in ankle ROM in our study patients was probably due to the sustained stretching effect of the calf muscle brought about by the ankle-foot orthosis which in turn controls the calf muscle spasticity and allowed more functional ROM during gait.…”
Section: Discussionmentioning
confidence: 50%